Clandestinovirus: A Giant Virus With Chromatin Proteins and a Potential to Manipulate the Cell Cycle of Its Host Vermamoeba vermiformis - Rolland, Clara; Andreani, Julien; Sahmi-Bounsiar, Dehia; Krupovic, Mart; La Scola, Bernard; Levasseur, Anthony (Frontiers in Microbiology, 2021)
For several decades, the vast world of DNA viruses has been expanding constantly. Various discoveries in this field have broadened our knowledge and revealed that DNA viruses encode many functional features, which were once thought to be exclusive to cellular life. Here, we report the isolation of a giant virus named “clandestinovirus”, grown on the amoebal host Vermamoeba vermiformis. This virus was discovered in a mixed co-culture associated with another giant virus, Faustovirus ST1. Clandestinovirus possesses a linear dsDNA genome of 581,987 base pairs containing 617 genes. Phylogenetically, clandestinovirus is most closely related to Acanthamoeba castellanii medusavirus and was considered a member of the proposed Medusaviridae family. However, clandestinovirus genome is 65% larger than that of medusavirus, emphasizing the considerable genome size variation within this virus family. Functional annotation of the clandestinovirus genes suggests that the virus encodes four core histones. Furthermore, clandestinovirus appears to orchestrate the cell cycle and mitochondrial activities of the infected host by virtue of encoding a panel of protein kinases and phosphatases, and a suite of functionally diverse mitochondrial protein homologs, respectively. Collectively, these observations illuminate a strategy employed by clandestinovirus to optimize the intracellular environment for efficient virus propagation.